UPAYA PENERTIBAN PARKIR OLEH DINAS PERHUBUNGAN KABUPATEN BENGKALIS DIKAWASAN PERKOTAAN KOTA BENGKALIS - Juwandi Juwandi; Ade Idra Suhara (STAIN Bengkalis, 2020)
The development of Bengkalis Regency from to year has caused an increase in people’s lifestyles, one of which affects the vehicle ownership sector in Bengkalis Regency which in increasing. The vehicle does not always move, there are times when the vehicle stops, making the parking lot the most important element in transpormation. The high public demand for parking order is made a regulation that can improve parking order to the maximum, namely through Bengkalis District Regulation Number 1 of 2016 concerning Public Order. Parking problems that often arise is the practise of careless parking at the edge of the road which causes congestion. The main problem in this study is how to control careless parking by the Bengkalis District Transportation Office in Jalam Jendral Sudirman and Jalan Tengku Umar and what are faced in controlling. The research method used is a qualitative method by collecting data through interviews and documentation conducted to informants who are considered competent in providing information. The results showed that Bengkalis District Transportation Departement had not been maximized in controlling using the repressive and preventive pilicies of indiscriminate parking. And obstacles in the effort to control careless parking by the Bengkalis District Transportation office on Jalan Jenderal Sudirman and Jalan Teuku Umar are the lack of awareness of the people in Bengkalis Regency in obeying traffic signs and the lack of personnel owned bt Dishubkominfo in efforts to control careless parking at Jalan Jenderal Sudirman and Jalan Teuku Umar in Bengkalis Regency. Keywords: Control, Random Parking, Transportation Department, Preventive Efforts, Repressive Efforts.